Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting - December 3, 2021. (Policy Papers; Policy Paper ;, 2021)
This Work Program puts forward an IMF Board agenda focused on activities of critical importance to our members. In line with the strategic directions laid out in the Fall 2021 Global Policy Agenda and the International Monetary and Financial Committee (IMFC) Communique, the Work Program supports three policy priorities: (i) vaccinate the world to combat the pandemic everywhere; (ii) calibrate bilateral and multilateral policies to support the recovery and reduce scarring and divergences; and (iii) accelerate the transformation of the global economy to make it greener, more digital, and inclusive. To deliver on this agenda, it is also important to ensure that the Fund remains appropriately equipped to maintain its role at the center of the global financial safety net.